Finite element modeling of non-loaded reinforced concrete one-way slab exposed to fire / Norlizan Wahid and Tim Stratford - Wahid, Norlizan; Stratford, Tim (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
A study on the reinforced concrete slab behaviour at a high temperature can be done by modelling the structure using the finite element method. Different types of elements can be used to model the slab, but the effectiveness of each of the elements and the differences in the results obtained need to be studied. This study examined the differences in results obtained from the slab model built from different types of elements available in the finite element analysis. A non-loaded 250 mm thick one-way reinforced concrete slab exposed to ISO834 fire, from the study by Cooke (2001) [1], was analysed using the finite element method in Abaqus. The model builds with three different types of elements, namely plane strain, shell elements and solid elements, to distinguish their ability in predicting the slab behaviour at high temperatures. reasonablyThe mesh convergence study determined the optimum size of each element that could well predict the slab deflection within a reasonable time. A coarser mesh size of solid elements was chosen because of the computational cost limitation. The results demonstrate that different types of elements do not give a significant difference in producing temperature profiles. The slab deflection predicted by the three elements were close and comparable with the test results.